Elderly Life in a Changing Society: A Case Study of Sahid Lakhan Gaupalika, Gorkha - K.C., Arjun (Kutumbha vani, 2023)
The contemporary society, the elderly continue experiencing various challenges and wins due to rapid social transformations. This research explored the geriatric respondents’ quality of life in the context of dynamic social change in Sahid Lakhan Gaupalika, Gorkha, Nepal. With a convenience sample of 37 elderly participants, this qualitative study examined the impact of socio-economic change on the participants’ quality of life, more specifically in the areas of health, social support, financial stability, and healthcare insurance. The challenges learnt about older persons were; poor health with half of the elderly persons having no access to health facilities. 65% reporting inadequate facilities. Social isolation affected 54. 5 percent by the result of the migration phenomenon of young family members to urban areas. Economic instability was observable manifested in that 51 percent of the households experienced some form of economic turnover. 35% of the households reported that they had no regular sources of income, 27. 03% depended on pensions and 21. 62% on remittances. However, the backbone of help came from within the community structures and non-governmental organizations as 37. 31% regard themselves as connected with their community or else strongly connected and ... 84% of those respondents. 43 percent of which they get assistance from local actors. This paper proves that friend and neighbor support systems are crucial in preventing negative change effects experienced by the elderly population. It identified the need for better health care facilities, strong supporting frameworks for promoting the elderly’s quality of life and strong economic policies for the advancement of the elderly living poor rural life in Nepal. Such ideas are crucial for policy makers, social workers and other organizations that want to develop and implement efficient related programs and policies on similar environments for the elderly.